RISK FACTORS ASSOCIATED WITH FRACTURE OF THE LUMBOSACRAL SPINE AND ITS COMPROMISE IN THE QUALITY OF LIFE OF CIRRHOTICS - Mariana de Morais Lira Gouvea SIQUEIRA; Luiz Augusto CASULARI; Wladimir Magalhães de FREITAS; Marcos de Vasconcelos CARNEIRO; Liliana Sampaio Costa MENDES (Arquivos de Gastroenterologia, 2022)
ABSTRACT Background Chronic hepatic disease is associated with osteoporosis, osteopenia or osteomalacia. Osteoporosis and fractures due to bone fragility present high prevalences and are more frequent in patients with liver cirrhosis than in the general population. The search for a diagnosis of osteopenia and osteoporosis in this population may allow early intervention and modify unfavorable outcomes. Objective To know the prevalence of osteopenia or osteoporosis and of fracture due to bone fragility in individuals with liver cirrhosis, the associated risk factors, and its compromise in their quality of life (QoL). Methods Observational, transversal study performed with 71 liver cirrhosis patients of the Hepatology Service of the Hospital de Base do Distrito Federal, Brasília, DF, Brazil, between July 2017 and December 2018. The patients were submitted to bone densitometry (DXA) of the lumbar spine and of the femoral neck, to x-ray of the lumbosacral spine and to the Chronic Liver Disease Questionnaire (CLDQ) for the evaluation of quality of life (QoL). The Fracture Risk Assessment (FRAX) major was calculated for patients >50 years old. The analyses were performed for the evaluation of the risk factors associated with lumbosacral spine fracture. Results The majority (62%) of the 71 evaluated patients was diagnosed with osteoporosis or osteopenia on DXA. Of the 44 patients with osteopenia or osteoporosis, 52.3% were female, with a mean age of 62.6±9.51 years old, with the majority (72.7%) being Child A, cirrhotics of alcoholic etiology (36.4%), and with an intermediate QoL according to the CLDQ (3.3). Regarding the patients with lumbosacral spine fracture, the mean age was 61.6±11.1 years old, 60% were female, most of them Child A (66.7%), of alcoholic etiology (46.7%), and with an intermediary QoL according to the CLDQ (3.5). The presence of osteopenia and/or osteoporosis was associated with lumbosacral fracture (P<0.001), without correlation with the other analyzed variables: age, body mass index, gender, presence and absence of ascites, Child-Pugh classification, vitamin D, calcium, and phosphorus serum concentration, cirrhosis etiology and FRAX major. Conclusion The prevalence of hepatic osteodystrophy was high, and the occurrence of lumbosacral spine fracture was more associated with osteoporosis and/or osteopenia among the cirrhotic patients studied. The QoL was intermediate and with no differences between cirrhotics with and without fracture.